Peran BUMDes dalam Peningkatan Kesejahteraan Masyarakat: Studi Kasus di Gampong Meurandeh, Langsa - Rowend F. Sitorus; Putri Keken Manik; Ivandi Rangkuti; Puji Marsola; Asmaul Mauliza; Putri, Desyana (Universitas Katolik Widya Karya Malang, 2025)
This research aims to explore the role of Village-Owned Enterprises (BUMDes) in improving the welfare of the community in Gampong Meurandeh, Langsa City, as well as to provide an overview that can serve as a reference for other BUMDes with similar characteristics. This study uses a descriptive qualitative method with an inductive approach to obtain in-depth and contextual data. Data were collected through observations, documentation, and interviews with the Village Head, village officials, and BUMDes administrators. The research findings show that BUMDes Sejahtera contributes positively to the community's welfare through an active business unit for party equipment rentals that still operates and can absorb local labor. However, the cooperative savings and loan business unit of this BUMDes has experienced a decline in operational activities, which poses a challenge in efforts to comprehensively improve community welfare. These findings emphasize the importance of business development strategies and capacity building for managers so that BUMDes Sejahtera can sustain itself and provide more optimal benefits for the welfare of the village community. Practically, the results of this study can serve as a reference for village governments and BUMDes managers in designing more adaptive and sustainable policies and business strategies.